Short-term speech-language intervention for children with disorders of the autism spectrum - Martins,Ligia Zanella (2013)
Purpose: To assess any changes in the Functional Communicative Profile (FCP) and in the Social Cognitive Performance (SCP) of children with Autism Spectrum Disorders, based on two short periods of intervention. Methods: The study was conducted with 21 children with Autism Spectrum Disorder diagnoses, randomly allocated into two groups, who received the same short-term intervention types (6 weeks with the mother and 6 weeks with the support of an educational software program). The intervention process was conducted by speech-language pathologists who were part of a graduate program in this area. Results: Samples of 15-minute interaction sessions between the child and speech-language pathologist were used to assess the changes in the FCP and the SCP. The statistic analysis pointed out differences only in Group 1 for the variables “percentage of communicative space used” and “use of the mediating object”. Conclusion: With the intervention sessions structured over 12 weeks, it was possible to observe a few changes in the children's FCP and in the SCP. Therefore, we point out the need for new research studies of longer duration.